Ketidakpatuhan Wajib Pajak dalam Aksi Korporasi yang Berpotensi Menurunkan Penerimaan Pajak Negara - Rahmat Heryat Furqon; Azhar Affandi; Dadang Suwanda (Universitas Batanghari Jambi, 2022)
Tax revenue is one of the sources of state financing. The achievement of the tax revenue target can be achieved if the taxpayer is obedient in carrying out his tax obligations. This study aims to see the level of compliance of corporate taxpayers with corporate action consisting of merger, consolidation, expansion or takeover of taxpayers' businesses on tax revenues. The research design approach used is descriptive qualitative research, which is research that aims to make a systematic, factual, and accurate description of the facts and characteristics of the research population. The data collection tool used in this research is document study. The results of this study indicate that the level of taxpayer compliance in corporate actions related to mergers, consolidations, expansions or takeovers is still low so that state tax revenues are not optimal.